Analysis of complications in type 2 diabetes mellitus patients at Ibnu Sina Hospital in 2023 - Handayani, Dewi Sri; Vitayani, Sri; Harahap, Muhammad Wirawan; Gani, Azis Beru; Nur, Muh Jabal (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a metabolic disorder characterized by hyperglycemia due to decreased insulin secretion or insulin resistance. T2DM can lead to microvascular complications, such as neuropathy, nephropathy, and retinopathy, as well as macrovascular complications, including heart disease, stroke, and peripheral vascular disease. Objective: This study aimed to determine the relationship between age, gender, HbA1c levels, and the duration of T2DM with the complications experienced by T2DM patients at Ibnu Sina Hospital Makassar. Method: This was a descriptive observational study with a cross-sectional design involving 40 T2DM patients. Data were collected using secondary patient records. Results: The most common complication found was diabetic neuropathy, affecting 19 patients (47.5%). Statistical analysis using the chi-square test showed a significant relationship between age and complications (p = 0.002) and between HbA1c levels and complications (p = 0.004). Gender showed no significant relationship with complications. The duration of T2DM could not be analyzed due to incomplete data. Conclusion: Age and HbA1c levels are significantly associated with the occurrence of complications in T2DM patients at Ibnu Sina Hospital in 2023. Regular monitoring and strict glycemic control are essential to minimize the risk of complications.